Locking plate fixation in pediatric femur fracture: evaluation of the outcomes in our experience - Vitiello, Raffaele; Lillo, Marco; Donati, Fabrizio; Masci, Giulia; Noia, Giovanni; De Santis, Vincenzo; Maccauro, Giulio (Acta Biomedica Atenei Parmensis, 2019)
Background and Aim: Femoral shaft fracture is a common traumatic musculoskeletal injures in pediatric population. The treatment of diaphyseal femoral fractures depends on age patient and pattern fracture. We present our record about the use of locking plate fixation and their outcomes. Method: We conduct a retrospective analysis in 22 patients, surgically treated for 26 diaphyseal femur fracture between 2008 and 2013. The mean age was 13 years. All the patients underwent a clinical and radiological follow-up for two years. We recorded time to weight bearing, time to union, complication (malalignment, dysmetria, infection), time to resumption to sport, plate removal, parents’ satisfaction. Results: All the patients had a minimal clinical e radiological follow-up of 24 months. The average fracture healing time was of 7.4 weeks. All the patients had a full hip and knee range of movements. Fifteen patients developed minor malalignment (varovalgus or procurvatum femur) without clinical effects. No cases of infections. The mean time to a full weight bearing was 12 weeks and the return to sportive activity was 24 weeks. Four patients required a plate and screws removal. The average result of parents’ satisfaction was 8/10. Conclusions: Locking plate fixation is to be considered a successful way of treatment for pediatric femur fractures, especially in patients older than 6 years, head-injured or in the treatment of polytrauma. The anatomic and functional outcomes are comparable to those of other fixation techniques for this kind of fracture.